The Comparison of the Immediate Effect of 3 Functional, UCBL and Modified UCBL Foot Orthotics Impact on Dynamic Balance in Subjects with Flexible Flatfoot - Somayyeh Paiehdar; Hassan Saeedi; Amir Ahmadi; Mohammad Kamali; Maryam Mohammadi (University of Social Welfare and Rehabilitation Sciences, 2014)
Objective: Previous studies have showed that Flatfoot as flattened out or lowered medial longitudinal arch of foot, may increase foot injuries during functional activities like walking. As foot orthotics widely is prescribed for the control of flatfoot. Mechanism of these devices' effects on balance are not fully clear yet and need to be evaluated and quantified by using proper instruments beside clinical observations. Purpose: The purpose of this study was to evaluate and compare the immediate effect of UCBL, Functional and Modified UCBL foot orthosis on dynamic balance of subjects with Flexible Flatfoot Materials & Methods: Twenty men and wemen young adults (23.5) with flexible flatfoot were recruited. Subjects were recruited using non-probability sampling and sample available. Participants performed balance tests in 4 conditions: with shoes, shoes with functional insole, UCBL and modified UCBL foot orthosis on Biodex Balance System. In each of this conditions, total, medial-lateral and anterior-posterior balance sways were recorded and then evaluated. Repeated measures ANOVA test was used for analysis of data. Results: The results of this study showed that Total sways in functional and UCBL insoles were significantly lower than modified UCBL.(P<0.05). But, A-P and M-L sways had not any significant difference in three orthoses. The comparsion of shoe and orthoses results showed no significant difference in total, A-P and M-L directs. Conclusion: Regarding that total sways in the UCBL and Functional insoles is lower than modified UCBL, seems to be due to orthoses structural differences, and may improve balance in people with flexible flatfoot orthotics. No significant differences were in balance indexes between shoe and orthoses and showed that shoe can decrease postural sways lonely, because of shoe effects, orthoses could not affect balance capacity whitout adaptations.